Better Than Bullet Points : Creating Engaging e-Learning with PowerPoint. - Bozarth, Jane (Wiley, 2013)
Featuring a complete update of the previous edition to reflect the new and expanded tools of PowerPoint 2013. By providing in-depth guidance, specific instructions, and helpful exercises, the book helps everyday trainers to create potent e-learning through the readily available popular desktop application. Established expert Jane Bozarth guides readers through the powerful new and updated features of the soon-to-be-released 2013 version, covering everything from text to art, animation to interactivity. If you have PowerPoint, this book will immediately put free real-world tools in your hands.